Prospective evaluation of ADAMTS-13 and von Willebrand factor multimers in cardiac surgery. Issue 8 (December 2016) - Reinecke, Imke R.; Weber, Christian F.; Budde, Ulrich; Seifried, Erhard; Miesbach, Wolfgang A.
Abstract : Acquired thrombotic–thrombocytopenic purpura, one of the main representatives of thrombotic microangiopathies (TMAs), is caused by the accumulation of antibodies against ADAMTS-13. Several cases of postoperative TMAs have been observed during the past few years, but the pathogenesis remains unknown. In addition to this, it is unclear whether the use of extracorporeal circulation (ECC) during cardiac surgery has an influence on the occurrence of cardiac surgery-associated TMA. In this study, we investigated the relationship between ADAMTS-13 (a disintegrin and metalloprotease with thrombospondin type 1 motifs 13), ADAMTS-13 inhibitor, von Willebrand factor (VWF) and large VWF multimers in cardiac surgery with and without the use of ECC. Blood samples were taken preoperatively, intraoperatively and up to 6 days postoperatively. A total of 47 patients (median age 70 years, 18 women, 29 men) undergoing cardiac surgery were included; cardiac surgery with the use of ECC (cardiopulmonary bypass) was used in 39 patients, and the off-pump coronary artery bypass technique was used in eight patients. TMA was not diagnosed in any of the patients. Cardiac surgery led to a significantly reduced ADAMTS-13 activity (from 67 to 51%, P < 0.001 in the cardiopulmonary bypass group, from 64 to 48%, P = 0.02 in the off-pump coronary artery bypass group) and higher amounts of large VWF multimers. Development of ADAMTS-13 antibodies was not induced by cardiac surgery. Cardiac surgery led to a slight but significant decrease of ADAMTS-13, but this decrease was not associated with TMA.